Effectiveness of the microcredit program in enhancing micro-enterprise entrepreneurs' income in Selangor - Mohd Tammili, Fatin Najiha; Mohamed, Zainal Abidin; Terano, Rika (Canadian Center of Science and Education, 2018)
Poverty has been one of the pressing issues in developing countries like Malaysia. Amanah Ikhtiar Malaysia (AIM) was the first microcredit institution and one of the dominant players contributing to the poverty eradication in Malaysia through the provision of microcredit to the poor. Thus, the study aimed to investigate the effectiveness of the microcredit program on poverty eradication as experienced by AIM microcredit recipients in Selangor. Systematic random sampling was conducted to sample 326 Sahabat (from this point onwards the AIM microcredit recipients will be known as Sahabat) from February to April 2016. Descriptive analysis and multiple regression were used to analyse the data distribution and relationship between the dependent variable as measured by income-investment ratio and independent variables represented by socio-demographic as well as other related variables necessary to achieve the study objective. The findings of the study show that most of Sahabat were married (95.7 percent) and have secondary educated (72.7 percent). In terms of income distribution, most Sahabat earn less than RM1,500.00. Nevertheless, all Sahabat showed positive income changes after receiving different microcredit program schemes from AIM. Multiple regression analysis have identified two variables which are the family workers and hired workers where both significantly influenced the income-investment ratio after joining the microcredit program. This study affirmed the effectiveness of the AIM program in poverty eradication among the poor. AIM also plays an important role in meeting the financial needs of Sahabat which is necessary to enhance their microenterprises.